2012
DOI: 10.1016/j.ajpath.2012.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cripto-1 during Epithelial-to-Mesenchymal Transition in Development and Cancer

Abstract: Epithelial-to-mesenchymal transition (EMT) is a critical multistep process that converts epithelial cells to more motile and invasive mesenchymal cells, contributing to body patterning and morphogenesis during embryonic development. In addition, both epithelial plasticity and increased motility and invasiveness are essential for the branching morphogenesis that occurs during development of the mammary gland and during tumor formation, allowing cancer cells to escape from the primary tumor. Cripto-1, a member o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 92 publications
9
94
0
7
Order By: Relevance
“…HOTAIR can also accelerate the degradation of Ataxin-1, which can activate the promoter of E-cadherin. E-cadherin is the key regulator of the EMT, as it regulates epithelial cell-to-cell interactions (54).…”
Section: Epithelial-to-mesenchymal Transition (Emt) and Maintenance Omentioning
confidence: 99%
“…HOTAIR can also accelerate the degradation of Ataxin-1, which can activate the promoter of E-cadherin. E-cadherin is the key regulator of the EMT, as it regulates epithelial cell-to-cell interactions (54).…”
Section: Epithelial-to-mesenchymal Transition (Emt) and Maintenance Omentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT), which was initially identified as a characteristic of morphogenesis during embryogenesis, is a transdifferentiation program that reprograms adherent epithelial cells into more phenotypical (2,18,19). Developmental genetics studies have revealed that the orchestration of EMT is critical to the development of malignant traits, such as motility, invasiveness, metastasis, dissemination and apoptosis-resistance in various tumor cells (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 3, the immunoblot assay shows expression levels of downstream molecules of brachyury, such as E-cadherin [46] and p-ERK [47], were elevated (day 6). ERK and β -actin were used as controls for protein quantification.…”
Section: Resultsmentioning
confidence: 99%